DYNAMICS OF INFORMATION CONFLICTS IN INTELLECTUAL SYSTEMS - Ignatov , V. O.; Guziy , M. M. (Problems of Informatization and Control, 2021)
A dynamic model of information conflicts in intelligent systems is proposed. The analysis of verbal, logical and mathematical methods of modeling information conflicts is carried out. A parametric analysis of the proposed model based on the solution of the system of differential-logical equations is performed.